NLRX1 functions as a tumor suppressor in Pan02 pancreatic cancer cells - Nagai-Singer, Margaret A.; Morrison, Holly A.; Woolls, Mackenzie K.; Leedy, Katerina; Imran, Khan Mohammad; Tupik, Juselyn D.; Allen, Irving C. (Frontiers in Oncology, 2023)
Pancreatic cancer is a deadly malignancy with limited treatment options. NLRX1 is a unique, understudied member of the Nod-like Receptor (NLR) family of pattern recognition receptors that regulates a variety of biological processes that are highly relevant to pancreatic cancer. The role of NLRX1 in cancer remains highly enigmatic, with some studies defining its roles as a tumor promoter, while others characterize its contributions to tumor suppression. These seemingly contradicting roles appear to be due, at least in part, to cell type and temporal mechanisms. Here, we define roles for NLRX1 in regulating critical hallmarks of pancreatic cancer using both gain-of-function and loss-of-function studies in murine Pan02 cells. Our data reveals that NLRX1 increases susceptibility to cell death, while also suppressing proliferation, migration, and reactive oxygen species production. We also show that NLRX1 protects against upregulated mitochondrial activity and limits energy production in the Pan02 cells. Transcriptomics analysis revealed that the protective phenotypes associated with NLRX1 are correlated with attenuation of NF-κB, MAPK, AKT, and inflammasome signaling. Together, these data demonstrate that NLRX1 diminishes cancer-associated biological functions in pancreatic cancer cells and establishes a role for this unique NLR in tumor suppression.